Comparative Analyses of Poly(ethylene 2, 5‐furandicarboxylate) − PEF − and Poly(ethylene terephthalate) − PET − Resins and Production Processes. Issue 1 (15th October 2018) - Gomes, Frederico W.; Lima, Rafael C.; Piombini, Carolinne R.; Sinfitele, Jorge F.; de Souza, Fernando G.; Coutinho, Paulo L. A.; Pinto, José Carlos
Abstract : The increasing interest in environment friendly products and processes has encouraged studies on the production of polymers from renewable sources. In this context, poly(ethylene 2, 5‐furandicarboxylate) − PEF − is regarded as a potential alternative for poly(ethylene terephthalate) − PET − resins. However, despite the increasing number of studies on PEF synthesis and characterization, there is still room for comparisons between processes used to produce PEF and PET and between some characteristics of the produced resins. For this reason, in the present work PEF was produced through direct esterification and through transesterification, whilst PET was synthesized through transesterification, to allow comparative analyses of the respective process performances. Results indicate that PEF can be produced at milder and simpler operation conditions, although PEF processing is much more difficult, since PEF is less stable to heat, melts at lower temperatures, is more crystalline and is much more rigid than PET, indicating that appropriate modification of PEF resins is needed for the effective replacement of PET in real industrial applications.